From Traditional Contract to Digital Practice: Examining Istishna Contracts Applications in MSMEs Furniture Online Transactions - Dwi Safitri; Wartoyo Wartoyo; Diana Djuwita (CURRENT ADVANCED RESEARCH ON SHARIA FINANCE AND ECONOMIC WORLDWIDE, 2025)
This study examines the implementation of the Istishna contract within a pre-order (PO) business model and evaluates its compliance with Sharia accounting standards, specifically PSAK 403 and PSAK 404, at UMKM Duta Rotan. Employing a qualitative descriptive approach, the research captures the actual business practices through semi-structured interviews, direct observation, and analysis of transactional and supporting documents. The findings reveal that the enterprise’s pre-order system substantively reflects the core characteristics of the Istishna contract, particularly in the customization of goods prior to production based on agreed specifications. However, significant gaps persist in the financial reporting framework. Accounting practices remain rudimentary, limited to basic order recording without the preparation of comprehensive financial statements. Revenue recognition is conducted on a cash basis, which diverges from the accrual-based approach prescribed under Sharia accounting standards. Additionally, the absence of systematic recording for production costs and inventory results in incomplete and potentially misleading financial information. This study highlights a critical disconnect between operational adherence to Islamic contractual principles and the formal accounting practices required for Sharia compliance. It underscores the urgent need for capacity building in Sharia-based financial reporting, particularly among micro, small, and medium enterprises (MSMEs). Strengthening accounting practices is essential not only to ensure regulatory compliance but also to enhance transparency, accountability, and long-term sustainability in line with Islamic economic principles.